Proximate Analysis, Glycemic Index, and Glycemic Load in Gulo Puan: A Culinary Investigation of a Traditional Dish from Pampangan, South Sumatra - Ningsih, Windi Indah Fajar; Fitriani, Uthfi Aulia; Ramdika, Sari Bema; Harwanto, Fatria (Universitas Airlangga, 2024)
Gulo Puan, originating from Pampangan, South Sumatra, stands out as one of the region's specialties. Crafted from buffalo milk and sugar, Gulo Puan boasts a delightful combination of sweet and savory flavors. Locally embraced, this delicacy is commonly enjoyed as a snack or incorporated into various culinary preparations. This study's primary objective was to comprehensively analyze the proximate content, glycemic index, and glycemic load of Gulo Puan. Employing an experimental quantitative research approach, the proximate analysis took place in the GIS laboratory, while the study of glycemic load and glycemic index involved 15 participants selected through purposive sampling. The results of the proximate study, presented descriptively, revealed the following composition in Gulo Puan: total energy (417.44 kcal), carbohydrate (55.93%), fat (16.65%), protein (10.25%), ash (1.64%), and water (15.03%). Comparisons of glycemic index between Gulo Puan (88.69%) and brown sugar (95.05%) exhibited a statistically significant average difference (p-value 0.004 (<0.05)). Similarly, a comparison of glycemic load between Gulo Puan (44.34%) and brown sugar (47.52%) also demonstrated a significant average difference (p-value 0.004 (<0.05)).